REVITALISASI DEWAN PENGAWAS SYARIAH (DPS) PADA LEMBAGA EKONOMI SYARIAH - Iska, Syukri (JURIS (Jurnal Ilmiah Syariah), 2012)
Sharia Supervision Board (Dewan Pengawas Syariah) plays very strategic roles insharia economic institutions. Since its main roles will give influences, such as toguarantee the safety of ummah in one side due its appropriateness in taking anydecisions and economic practices which are always based Islamic laws, this board will keep the credibility of the institution. This is quite reasonable since ummah believe that those institutions have been run based on Islamic laws. Consequently, Sharia Supervision Board needs revitalizing to optimalize such strategic roles.